EAGER EXSPECTATION DAN MOTIVASI MAHASISWA JURUSAN KOMUNIKASI DAN PENYIARAN ISLAM IAIN SALATIGA - Mukti Ali (INJECT (Interdisciplinary Journal of Communication), 2016)
This article reveals about self motivation of KPI Student and study on new courses, both in psychological and social and social anthropologist confronting a range of very different situations. The psychological and social situation diversity and social anthropologist of KPI students is closelyrelated to motivation and expectation which is varied. There is also the motivation from student to fulfill the knowledge of the world of communications and broadcasting which is related with the educational background of his secondary education, or he wants to continue his hobby in the broadcasting world. Dealing with the eager expectation or the big dream of KPI Student is divided into some expectation; The hope dealing with the learning process and supporting material from the learning process, and the expectation of their future after graduating from this department as a Bachelor of communication and broadcasting connected with employment chance the expectation in the process of teaching or educating for example, most students of KPI IAIN Salatiga needs somefacilitation dealing with communications technology and the broadcasting technology such as, cameras, handy camp, and radio station.